Stable isotope labeling confirms mixotrophic nature of streamer biofilm communities at alkaline hot springs - Schubotz, Florence; Hays, Lindsay E.; Meyer-Dombard, D'Arcy R.; Gillespie, Aimee; Shock, Everett L.; Summons, Roger E. (Frontiers in Microbiology, 2015)
Streamer biofilm communities (SBC) are often observed within chemosynthetic zones of Yellowstone hot spring outflow channels, where temperatures exceed those conducive to photosynthesis. Nearest the hydrothermal source (75-88°C) SBC comprise thermophilic Archaea and Bacteria, often mixed communities including Desulfurococcales and uncultured Crenarchaeota, as well as Aquificae, Thermus, each carrying diagnostic membrane lipid biomarkers. We tested the hypothesis that SBC can alternate their metabolism between autotrophy and heterotrophy depending on substrate availability. Feeding experiments were performed at two alkaline hot springs in Yellowstone National Park: Octopus Spring and ‘Bison Pool’, using various 13C-labeled substrates (bicarbonate, formate, acetate and glucose) to determine the relative uptake of these different carbon sources. Highest 13C uptake, at both sites, was from acetate into almost all bacterial fatty acids, particularly into methyl-branched C15, C17 and C19 fatty acids that are diagnostic for Thermus/Meiothermus and some Firmicutes as well as into universally common C16:0 and C18:0 fatty acids. 13C-glucose showed a similar, but a 10 to 30 times lower uptake across most fatty acids. 13C bicarbonate uptake, signifying the presence of autotrophic communities was only significant at ‘Bison Pool’ and was observed predominantly in non-specific saturated C16, C18, C20 and C22 fatty acids. Incorporation of 13C-formate occurred only at very low rates at ‘Bison Pool’ and was almost undetectable at Octopus Spring, suggesting that formate is not an important carbon source for SBC. 13C uptake into archaeal lipids occurred predominantly with 13C acetate, suggesting also that archaeal communities at both springs have primarily heterotrophic carbon assimilation pathways. We hypothesize that these communities are energy-limited and predominantly nurtured by input of exogenous organic material, with only a small fraction being sustained by autotrophic growth.